Gross and Microscopic Prevalence of Tuberculosis in Cattle Slaughtered in Maiduguri Central Abattoir, Nigeria - Francis Enenche Ejeh; Zainab Biu; Fatima Lawan; Yasheruram Shettima; Yusuf Lekko (Journal of Applied Veterinary Science And Technology, 2026)
Background: Significant economic implications and public health concerns are posed by Bovine Tuberculosis (BTB), a critical zoonotic disease caused by Mycobacterium bovis. Within Nigerian abattoirs, substantial rates of meat and carcass condemnation are attributed to this infection. Purpose: Investigation was undertaken to report the prevalence of tuberculosis in cattle slaughtered at the Maiduguri Central Abattoir (MCA) through the utilization of post-mortem examination, Ziehl-Neelsen (Z-N) staining, and histopathology. Method: A cross-sectional survey of BTB lesions was conducted among cattle slaughtered at the MCA. Collected lesions were subjected to processing for acid-fast microscopy and histopathological analysis. Statistical evaluation of the obtained data was performed using IBM SPSS version 27, while Chi-square tests were employed to determine differences in BTB prevalence across various variables. Results: Examination for tuberculous lesions was carried out on two hundred and one slaughtered cattle, comprising 45.8% (92/201) males and 54.2% (109/201) females. Tuberculous lesions were identified in 7.0% (14/201) of the examined carcasses. Regarding breed distribution, the highest frequency of BTB lesions was observed in the Abori breed (50.0%), whereas no visible lesions were detected in the Ambala and Wadara breeds. A prevalence of 4.9% (10/201) was further demonstrated through the Ziehl-Neelsen staining technique. Histologically, leukocytic infiltration of granulomas accompanied by fibrosis was observed in the affected tissues. Conclusion: Persistent prevalence of bovine tuberculosis is confirmed in cattle destined for human consumption at the MCA. Given the zoonotic nature of the disease, an urgent necessity exists to scale up preventive and control measures to enhance public health safety.